Liberia : Ad Hoc Review Under the Extended Credit Facility Arrangement and Request for Augmentation of Access and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Background. With the highest number of new and cumulative Ebola cases recorded to date, Liberia is the country most affected by the epidemic in West Africa. In addition to exacting a heavy human toll, the Ebola outbreak is having a severe economic and social impact, and could jeopardize the gains from a decade of peace. The largest sectors of the economy (agriculture, services and mining) have been weakened by the epidemic, resulting in significant financing gaps for the fiscal and external accounts. The closure of international borders and, in particular, the internal quarantines are disrupting labor and food supply, leading to shortages of basic commodities, depreciation pressures and higher inflation. Request. The authorities are requesting an ad-hoc augmentation of access under the ECF and an immediate additional disbursement of SDR 32.3 million, equivalent to 25 percent of quota, to help bridge the significant financing need that has emerged in the wake of the outbreak. The authorities are also requesting modification of end-December performance criteria to allow on-lending of the equivalent of the Fund support to the government. Appraisal. Staff supports the authorities' request for an augmentation of access and immediate disbursement in light of the urgency and size of the balance of payments need. Staff also supports the requested modification of end-December 2014 performance criteria via a program adjustor to allow the on-lending of the additional Fund support to the government. Program status. The third ECF review was concluded on July 3, 2014. Available information indicates that the program remains on track and that continuous PCs are being met. Program financing. The proposed augmentation would complement assistance committed by other stakeholders including USD 19 million in additional budget support from the African Development Bank and the World Bank, and would help catalyze support from other donors. The authorities have committed to take the necessary measures to address any residual financing gap.